2021
DOI: 10.1021/acs.jpcc.1c03997
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Background Electrolyte Composition on the Interfacial Formation of Th(IV) Nanoparticles on the Muscovite (001) Basal Plane

Abstract: Understanding the impact of actinide nanoparticle (NP) formation is important to assess radionuclide mobility in the environment. We combined surface X-ray diffraction (SXRD) and in situ AFM to investigate the previously reported unusual electrolyte effects on Th uptake on mica. At low [Th] (0.1 mM), interfacial structures show a broad Th electron density (∼50 Å). A linear decrease of Th uptake with decreasing hydration enthalpy of the electrolyte cation (Li+, K+, NH4 +, and Cs+) indicates a competitive effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…The mobility of REEs in the environment is largely controlled by their interactions with mineral surfaces. , Many studies have been carried out to assess the retention potential of major rock-forming minerals, such as quartz and micas for trivalent heavy metals M­(III), including REEs and trivalent actinides. The impact of pH, metal concentration, and ligands on the adsorption was investigated, and models have been developed to predict the fate of REEs. ,, Mechanistically, studies of ion adsorption on muscovite mica showed that multivalent ions tend to adsorb farther from the mineral surface than monovalent ions, which is related to multivalent ions’ ability to retain water molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mobility of REEs in the environment is largely controlled by their interactions with mineral surfaces. , Many studies have been carried out to assess the retention potential of major rock-forming minerals, such as quartz and micas for trivalent heavy metals M­(III), including REEs and trivalent actinides. The impact of pH, metal concentration, and ligands on the adsorption was investigated, and models have been developed to predict the fate of REEs. ,, Mechanistically, studies of ion adsorption on muscovite mica showed that multivalent ions tend to adsorb farther from the mineral surface than monovalent ions, which is related to multivalent ions’ ability to retain water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of pH, metal concentration, and ligands on the adsorption was investigated, and models have been developed to predict the fate of REEs. ,, Mechanistically, studies of ion adsorption on muscovite mica showed that multivalent ions tend to adsorb farther from the mineral surface than monovalent ions, which is related to multivalent ions’ ability to retain water molecules. Some ions, for example, Al­(III) and some actinides such as Pu­(III/IV) and Th­(IV), polymerize at the interface to form secondary-phase thin films or nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al [ 56 ] studied the competitive sorption of U(VI) and Th(IV) on triphosphate-crosslinked magnetic chitosan resins from solution and found that the sorption capacities of U(VI) and Th(IV) clearly decreased as compared with a single sorption system, suggesting that the U(VI) and Th(IV) competed on the same sorption sites of the resins. Neumann et al [ 10 ] used surface X-ray diffraction and in-situ AFM to study Th(IV) sorption on mica and the results showed a linear decrease of Th(IV) sorption with increase of electrolyte cations, indicating the competitive effect among Th(IV) and electrolyte cations on mica. Virtanen et al [ 57 ] investigated the sorption of Eu(III), Y(III) and Cm(III) from solutions, and the results showed that sorption of Eu(III) and Cm(III) sorption was obviously decreased and sorption pH-edge shifted to higher pH when the concentration of competing Y(III) was higher than 10 −4 mol/L.…”
Section: Competitive Sorptionmentioning
confidence: 99%
“…The coordination chemistry property information such as the coordination number, the bond distances of actinides with other ions, the valence change of actinides (reduction or oxidation), possible precipitation, and the formation of actinide oxide nanoparticles may be achieved through XAFS spectroscopy analysis. In the last decades, advanced spectroscopy techniques have been applied extensively to measure the species of actinides on solid–water interfaces [ 9 , 10 , 11 , 12 , 13 ]. Such information is very helpful in understanding the interaction mechanism of actinides at solid–water interface as the microstructures and species of actinides on mineral surfaces affect the mobilization and bioavailability of actinides.…”
Section: Introductionmentioning
confidence: 99%
“…While a large body of our understanding of ion–ion correlations is based on theoretical studies, , only a few experimental observations are able to gain an insight into these phenomena, which is attributed to three main reasons: (1) multivalent ions have a strong tendency toward hydrolysis, which leads to changes in the ion charge and speciation and the formation of metal-(hydr)­oxo-nanoparticles. ,,, (2) The functional groups of many mineral surfaces readily undergo (de)­protonation, leading to high temporal and spatial variations in charge density and distribution with changing solution compositions (e.g., pH). (3) Some minerals can form strong covalent bonds with cations, which dominate over weaker electrostatic interactions.…”
Section: Introductionmentioning
confidence: 99%